Development of novel nanofiber membranes for seawater desalination by air gap membrane distillation - Feng, Chaoyang (University of Ottawa (Canada), 2009)
Our world is facing water and energy shortage. As a relatively new process, membrane distillation (MD) is being investigated as a low cost and energy saving alternative to conventional separation processes such as distillation and reverse osmosis since 1990s. As a result of material limit, the development of membrane distillation has not yet come to the commercial scale. But, it has become a hopeful technology of the future. The objective of this research is to develop novel nanofiber membranes for seawater desalination by air gap membrane distillation (AGMD). The concept of novel nanofiber membranes is based on the electro-spinning technology. By using electro-spinning method, a highly hydrophobic material (PVDF, poly vinylidene fluoride) was spun to filaments with diameters in nanometer range. The PVDF nanofibers turn into a nanofiber non-woven mat or web and bring high hydrophobicity and a highly open pore structure. This further fulfils the requirements for the MD membranes with reduced mass transport resistance and temperature polarization. Thus, membranes with high MD fluxes are expected. In Part I of the current research, hydrophilic and hydrophobic polymers and a polymer blend (PVDF, PVDF/PVP, PS, PES, PEI, PVC, PC, PAN, Nomex (PA), PVA and Collagen) were used for electro-spinning to generate naonofibers and nanofiber membranes. The electro-spinning parameters that affect the structure and other properties of the membrane and the MD membrane performance were identified. They include spinning dope concentration, solution feed rate, spinning voltage and naonofiber collect distance. The electro-spinning parameters were then optimized for obtaining the best performance data. The PVDF nanofiber membranes were characterized by SEM, AFM, DSC, measurement of LEPw (liquid entry pressure of water), equilibrium contact angle and particle separation. It was found that the pore size of the PVDF nanofiber membrane was around 1.5 mum. The equilibrium contact angle of some nanofiber membranes were above 120°. It shows that the novel membranes have a very open pore structure and are highly hydrophobic. Those characteristics are exactly what are needed for MD membranes. In Part II of the current research work, a novel PVDF nanofiber membrane was tested for saline water desalination by AGMD (air gap membrane distillation). Desalination by AGMD was carried out for various sodium chloride concentrations in feed (1 to 22 wt%) at the feed solution and cooling water temperature difference of 60°C. Above 99% salt rejection and above 8 kg/m 2h flux was obtained. As well, ethanol/water separation was investigated by using 5 and 10 wt % aqueous ethanol solution. Two theoretical models were developed to simulate the AGMD process; the first model was developed to describe the AGMD process based on the mass and heat transfer through the membrane, while the second model deals with the transfer of volatile component through the air gap. The experimental flux value fits the second model very well. It shows that the air gap is the dominating stage for the heat transfer of the AGMD process. In an early stage of this work, polypropylene (PP) was chosen to prepare membranes of high hydrophobicity and high porosity for membrane distillation by a solution casting method. The results are reported in Appendix I. This method, even though novel, was not quite appropriate to fabricate membranes with hydrophobicity and porosity high enough for MD application. Howevere, the microporous PP membranes so prepared seem to have a great potential for other separation applications than MD.
Keywords: Engineering, Chemical.